(untitled) (Economic and Political Thought, 2016)
The article discusses the foundation of the Law and Justice’s foreign policy from the perspective of the year 2005. It deals with the issue of Polish historical policy and its role in foreign policy as well as the issue of political leadership. The article is also an attempt to compare the assumptions of the foreign policy of the Second Republic of Poland and Józef Piłsudski’s camp to the Law and Justice’s foreign policy.